LEGAL CHALLENGES AND OPPORTUNITIES IN ECONOMICS AMID GLOBAL INTEGRATION AND TECHNOLOGICAL ADVANCEMENTS: A REVIEW OF THE REGULATORY FRAMEWORK - Gunawan Widjaja (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study discusses legal challenges and opportunities in the economy amid global integration and technological advances, with a focus on reviewing the regulatory framework. The dynamics of globalisation and digital technological innovation have brought significant changes to economic processes that require adaptive and responsive legal regulations. However, this study finds that legal uncertainty due to regulatory disparities between countries, weak law enforcement, and issues of cybersecurity and data protection are major challenges that hinder economic stability. On the other hand, technological advances provide opportunities to strengthen transparency, international collaboration, and the development of innovative technology-based regulations that can promote inclusive and sustainable economic growth. An in-depth literature review was used to explore these aspects as a basis for recommendations for updating an effective and equitable economic legal regulatory framework. The results of this study are expected to serve as a reference for policymakers and stakeholders in managing economic legal regulation in today's digital and global era.